PERKEMBANGAN RISET DAN PRODUK KOMERSIAL SISTEM PEMBERSIH PANEL SURYA - Malik Al Falah, Muhammad; Satya Kumara, I Nyoman; Ariastina, Wayan Gede (Jurnal SPEKTRUM, 2022)
The cleanliness of the solar panels is one of the factors that affect the energy production of a solar power plant. Solar panel cleaning is a solution to keep solar panels clean so that energy production can be optimal. This article reviews research developments and commercial products for solar panel cleaning, with the result showing various applicable techniques and commercial products for solar panel cleaning purposes. There are two distinct techniques used in solar panel cleaning, manual and automatic. The manual cleaning method is a method that conducts any action to operate the system manually by humans. The automatic cleaning method is a method that is controlled directly by the system without the need for human interference. Commercial solar panel cleaning products include telescopic poles equipped with brushes and water pumps, a robot that is permanently attached to the solar panel support construction equipped with dry clean and water clean methods, a robot with portable systems using long roller brushes, a convenient robot which has a remote vacuum cleaner system, to a mobile cleaning system using a robotic arm.